Visual analysis of acupoint massage applied to poststroke constipation based on CiteSpace - Li, Jiaji; Tang, Ling; Li, Ye; Xing, Xuanyu; Wang, Siyao; Hu, Shirong (Journal of integrative nursing, 2025)
The objective of this study is to analyze the relevant literature on acupoint massage applied to patients with poststroke constipation, to explore the research status, research hotspots, and research frontiers of poststroke constipation, and to provide reference for clinical practice and scientific research. With the help of CiteSpace software, the related literatures published in the China National Knowledge Infrastructure database on the application of acupoint massage to constipation after stroke were analyzed, and scientific atlas for visual analysis was drawn. The hot keywords in the field of acupoint massage for post-stroke constipation are constipation, nursing intervention, and traditional Chinese medicine (TCM) nursing, indicating the great importance of TCM nursing for such patients. In mutation word detection, words such as constipation, nursing, stroke, and defecation reflex have earlier mutation times. Massage is the keyword with the longest mutation time, suggesting it is an effective intervention for post-stroke patients and is widely recognized. The commonly used acupoints for poststroke constipation are Tianshu (ST 25), Zhongwan (CV 12), and Qihai (CV 6). These acupoints can regulate qi and blood and enhance gastrointestinal peristalsis, providing guiding significance for formulating relevant clinical practice guidelines. The research of acupoint massage in the nursing of poststroke constipation is still in the stage of practice and exploration, and the specific definition of operation process, technique, acupoint, time, and intensity is still not clear. Multicenter, large-sample, in-depth intervention research, and cohort studies hold immense significance for the future development of this discipline.